Inclusão escolar: equívocos e insistência - uma história de reis, príncipes, monstros, castelos, cachorros, leões, meninos e meninas - Batista, Cristina Abranches Mota (2012)
The demand for school inclusion of students with mental disabilities we face today has caused a great commotion for all of those involved, both students and their families and educators of regular schools and professionals of specialized institutions. This research aims to address this theme analyzing the diagnosis and definition of this disability. Along the way, we encountered the heavy load of studies and researches on this subject, which are characterized by the profound discrimination which has historically followed this disability, as well as the difficulties human beings face when dealing with it. As a result, studies and solutions provided by the modern with the purpose of achieving normative ideals had segregative characteristics. Thus, specialized actions were taken towards people diagnosed with a disability associated to an organic and incurable pathology. In addition, the mental disability was slowly identified as children s intellectual and developmental disabilities, which made it become a monopoly of behavioral and organicistic sciences. When discussing this theme, psychoanalysis introduced the matter of the subject, which triggered an actual subversion of how de disability was approached, making it possible to introduce the subject of the unconscious in a clinic filled with behavioral concepts. Thus, we analyzed the psychoanalytical approach on the inhibition and difficulties to advance in this study, with the purpose of going beyond the understanding of a simple cognitive deficit for this disability. Therefore we dedicated a chapter to the disability, on how the subject, in a weak position, builds social ties and how the subject faces instances of symbolic, imaginary and real. Analysis of contemporaneity was required so that we can understand the world where we live and the place occupied by the current inclusion movement. We verified that we live a moment when an anthropological turn is taking place, where both social life and according to some authors, the very psychic economy. Our time is characterized by the weakening of the Great Other, by the loss of legitimacy of the father figure, which evidently have consequences on the subject, and, not by chance, the disability is increased in this context. In our contemporaneity, specialized institutions created in order to enforce segregation are able to reverse this process taking part of inclusion and enabling the subject to leave that weak position. However, this possibility is created if they accept changing themselves and performing actions which include subjective issues, normative and homogenizing ideals. The last chapter explores school institutions and those institutions specialized in education, mastery and teaching, expressing our point of view that the inclusion will take place when the subject is included in all of these functions of an institution